2017
DOI: 10.1073/pnas.1703494114
|View full text |Cite
|
Sign up to set email alerts
|

Zbtb7b engages the long noncoding RNA Blnc1 to drive brown and beige fat development and thermogenesis

Abstract: Brown and beige adipocytes convert chemical energy into heat through uncoupled respiration to defend against cold stress. Beyond thermogenesis, brown and beige fats engage other metabolic tissues via secreted factors to influence systemic energy metabolism. How the protein and long noncoding RNA (lncRNA) regulatory networks act in concert to regulate key aspects of thermogenic adipocyte biology remains largely unknown. Here we developed a genome-wide functional screen to interrogate the transcription factors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(78 citation statements)
references
References 55 publications
1
74
0
Order By: Relevance
“…However, the exact residues, their upstream kinases, and the effects of hnRNPU phosphorylation on its biological functions remain currently unknown. Previous studies have demonstrated that hnRNPU interacts with a number of nuclear proteins including heterochromatin protein 1 alpha, the transcription factor Zbtb7b, and the long noncoding RNA Blnc1 . It is likely that regulation of these hnRNPU‐interacting factors may also underlie its effects on chromatin structure in response to physiological and pathophysiological stimuli.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the exact residues, their upstream kinases, and the effects of hnRNPU phosphorylation on its biological functions remain currently unknown. Previous studies have demonstrated that hnRNPU interacts with a number of nuclear proteins including heterochromatin protein 1 alpha, the transcription factor Zbtb7b, and the long noncoding RNA Blnc1 . It is likely that regulation of these hnRNPU‐interacting factors may also underlie its effects on chromatin structure in response to physiological and pathophysiological stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that hnRNPU interacts with a number of nuclear proteins including heterochromatin protein 1 alpha, the transcription factor Zbtb7b, and the long noncoding RNA Blnc1. (21,42,43) It is likely that regulation of these hnRNPU-interacting factors may also underlie its effects on chromatin structure in response to physiological and pathophysiological stimuli. Unlike transcriptional coactivators and repressors, the effects of hnRNPU inactivation on chromatin accessibility appeared to be bidirectional, suggesting that hnRNPU acts in a context-dependent manner to influence hepatic gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…If a candidate is lowly expressed, one can exogenously introduce a biotinylated form of the lncRNA using the RNA pull-down method, which we have successfully used to identify binding partners for lincRNA-Cox2. This has been performed for many lncRNAs [42,202,203].…”
Section: Subcellular Localization and Binding Partnersmentioning
confidence: 99%
“…Adding further confidence to the derived gene regulatory network, multiple of its less established member genes have been experimentally validated in recent studies. For example, ZBTB7B, which is linked to M1 in our network, has been reported as a potent driver of brown fat development and thermogenesis and cold-induced brite adipocytes formation (Li et al, 2017a). Multiple genes in M3, such as HOXC10, P53, NR2C2, SRF, MEF2C, and NR2F2 have been shown to negatively regulate Ucp1 (Kang et al, 2011;Li et al, 2009;Ng et al, 2017).…”
Section: Brite Adipogenic Gene Regulatory Networkmentioning
confidence: 80%